Living and working on the edge: 'Place precarity' and the experiences of male manual workers in a U.K. seaside town. Issue 8 (23rd February 2021) - Simpson, Ruth; Morgan, Rachel; Lewis, Patricia; Rumens, Nick
Abstract: Based on an ethnographic study of male manual workers in Blackpool, a large seaside town in the United Kingdom, and drawing on Bourdieu as a theoretical frame, this article explores the role of place in understanding conditions and experiences of precarity. With higher than average levels of deprivation, seaside towns have experienced particular employment challenges where precariousness is likely to be at the forefront of male manual workers' labour market condition. Results highlight the significance of the interplay between place, employment prospects, geographical 'constriction' and dispositions of 'provisionality, ' which, together, produce 'uneven geographies' of labour. We develop the concept of 'place precarity' to show how precarity is fundamentally rooted in the spatial context and to capture how conditions and experiences of precarity interact with localised employment conditions.